PENGARUH KEPUASAN KERJA DAN STRES KERJA TERHADAP KINERJA GURU DALAM MENGAJAR DI SMP NEGRI 2 KOLAKA - Ita Yulianti; M. Zakariah; Muhammad Akbar (Jurnal Teknologi Pendidikan Madrasah, 2023)
This research aims to determine job satisfaction and work stress on teacher performance in the learning context. Teachers are a key element in improving the quality of education, therefore, a deep understanding of the factors that influence their performance is essential.The research method uses a quantitative approach using a questionnaire as a data collection instrument. The respondents in this research were teachers from SMP Negeri 2 Kolaka. The collected data will be analyzed using statistical techniques, including regression to evaluate the relationship between job satisfaction, job stress and teacher performance. The research results obtained were that there was no influence of job satisfaction on teacher performance, with a value of sig. 0.816 > 0.05, while work stress has an influence on teacher performance, with a value of sig. 0.015 < 0.05. In this study, job satisfaction and job stress influenced teacher performance by 25%.